Cubic rings and their ideals - Drozd, Yu. A.; Skuratovskii, R. V. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We give an explicit description of cubic rings over a discrete valuation ring, as well as the description of all ideals of these rings.